2021
DOI: 10.1021/acsami.1c16367
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Controlling Drug Release by Light-Responsive Cholesteric Liquid Crystal Microcapsules Triggered by Molecular Motors

Abstract: Stimuli-responsive smart nanocarriers are an emerging class of materials applicable in fields including drug delivery and tissue engineering. Instead of constructing responsive polymer shells to control the release and delivery of drugs, in this work, we put forward a novel strategy to endow the internal drugs with light responsivity. The microcapsule consisted of molecular motor (MM)-doped cholesteric liquid crystals (CLCs) and drugs. The drug in gelatin-gum arabic microcapsules can protect the carried drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…66,67 LCEs, with stimuli-responsive shape-morphing properties, have demonstrated great promise for the applications of actuation, [68][69][70] soft robotics, [71][72][73] and controllable drug delivery. [74][75][76] In the field of tissue engineering and regenerative medicine, LCEs have also received intensive attention first because of their biomimetic architectures. 77 By engineering the orientations of LC moieties to resemble the anisotropic organizations between cells and extracellular matrix (ECM) fibrils in some biological tissues such as muscle, it could achieve directional alignments of cells on LCE-based scaffolds, [78][79][80] Diverse cellular functions (e.g., cellular function maturation 81 and stem cell differentiation 82 ) for facilitating tissue regeneration could be subsequently modulated.…”
Section: Lcesmentioning
confidence: 99%
“…66,67 LCEs, with stimuli-responsive shape-morphing properties, have demonstrated great promise for the applications of actuation, [68][69][70] soft robotics, [71][72][73] and controllable drug delivery. [74][75][76] In the field of tissue engineering and regenerative medicine, LCEs have also received intensive attention first because of their biomimetic architectures. 77 By engineering the orientations of LC moieties to resemble the anisotropic organizations between cells and extracellular matrix (ECM) fibrils in some biological tissues such as muscle, it could achieve directional alignments of cells on LCE-based scaffolds, [78][79][80] Diverse cellular functions (e.g., cellular function maturation 81 and stem cell differentiation 82 ) for facilitating tissue regeneration could be subsequently modulated.…”
Section: Lcesmentioning
confidence: 99%
“…To explore the potential applications of the OAMM‐driven droplet, our group prepared light‐directed microcapsules composed of OAMM 11 ‐doped CLC core and gelatin shell ( Figure a,b). [ 90 ] It was found that there was only negligible leakage of LC when dispersing the microcapsules in aqueous solution due to the protection of the polymer shell. By UV irradiation, the texture of CLC core rotated (Figure 9c), at the meantime, the LC molecules escaped from the inner core, illustrating that the morphology change of CLC core could accelerate the leakage of container.…”
Section: Oamm‐triggered Liquid Crystal Systemsmentioning
confidence: 99%
“…8CB and E7 represent commercial smectic LC with high viscosity and commercial nematic LC with low viscosity, respectively. a-e) Reproduced with permission [90]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…The usual approach is to disperse the CLCs and then cover the resulting droplets with a shell. Various methods have been developed to fabricate the shells of CLC microcapsules using CLC emulsion microdroplets as templates, such as in situ polymerization, , interfacial polymerization, complex coacervation, , and sol–gel methods . Compared to surfactant-stabilized conventional emulsions, solid particle-stabilized Pickering emulsions show better stability and sustainability and have been demonstrated to be a promising template to fabricate microcapsules. ,,, Cellulose nanocrystals (CNCs) are rod-like nanocelluloses and are normally extracted from wood pulp or cotton via acid hydrolysis. , CNCs display outstanding Pickering emulsifying ability due to their partial wettability with both oil and water phases.…”
Section: Introductionmentioning
confidence: 99%
“…The usual approach is to disperse the CLCs and then cover the resulting droplets with a shell. Various methods have been developed to fabricate the shells of CLC microcapsules using CLC emulsion microdroplets as templates, such as in situ polymerization, 31,32 interfacial polymerization, 33 complex coacervation, 34,35 and sol−gel methods. 36 Compared to surfactant-stabilized conventional emulsions, solid particle-stabilized Pickering emulsions show better stability and sustainability and have been demonstrated to be a promising template to fabricate microcapsules.…”
Section: Introductionmentioning
confidence: 99%